Has there been a weakening of environmentalism in Brazil - Andrade Júnior, José Roberto Porto de (Sustainability in Debate, 2025)
The article aims to discuss negative trends in environmentalism in Brazil over recent decades, particularly within civil society. The main research techniques employed are document analysis and the analysis of secondary data. The primary sources include the World Values Survey (WVS), Google Trends, and records of the creation of Brazilian parliamentary fronts. The findings indicate that Brazil has experienced: a decline in public confidence in the environmental movement; a decrease in the proportion of the population holding membership in environmental organisations; a drop in Google searches related to environmental topics; and reduced electoral success of environmentalist candidates. The discussion highlights that among the causes of this weakening of environmentalism in Brazil are the success of the anti-environmental movement and a shift in social priorities due to economic, political, and public health circumstances. It is also emphasised that these societal trends form part of the contextual backdrop that helps explain the dismantling of environmental policy in Brazil during the Bolsonaro administration (2019–2022).